A national review of the clinical use of group O D– red blood cell units. Issue 5 (1st February 2017) - Hirani, Rena; Wong, Janet; Diaz, Perfecto; Mondy, Phillip; Hogan, Chris; Dennington, Peta M.; Pink, Joanne; Irving, David O.
Abstract : BACKGROUND: There has been an international decline in the demand for red blood cell (RBC) units. In Australia, there has been a 21% reduction in demand between 2012 and 2015. In contrast, the demand for the "universal" group O D– RBC units is in fact proportionally increasing. STUDY DESIGN AND METHODS: The clinical use of the entire O D– RBC distribution for a 5‐week period throughout Australia was reviewed. Fate data on each unit issued (n = 9733) were collected that included the indication and urgency of transfusion, reason for discard, component age, and patient demographics. RESULTS: A total of 74% of audit forms were returned (n = 7143). The national discard rate of issued units was 7.9%. A total of 6387 units were transfused into an estimated total of 3008 patients (55% males) with median patient age of 67 years and median RBC age of 21 days. Forty‐seven percent were transfused to group O D– patients. A total of 17.4% were chosen for specific phenotype requirements, 24.5% of units were transfused close to expiry, and 24.5% were transfused into patients of other ABO groups. CONCLUSION: The data appear broadly representative of the current transfusion and inventory management practices surrounding the use of group O D– RBC units. Strategies to reduce O D RBC demand include reevaluation of inventory holdings particularly at smaller centers, increasing the panel of phenotyped RBC units across all ABO groups, more regular rotation of units between hospitals to minimize time expiry, and continuing education for promoting transfusion of ABO‐identical RBC units.